Our country friends [large type] : a novel - Shteyngart, Gary, 1972- (Random House Large Print, 2022)
"It's March 2020 and a calamity is unfolding. A group of friends and friends-of-friends gathers in a country house to wait out the pandemic. Over the next few months new bonds of friendship and love will take hold, while old betrayals will emerge among this unlikely cast of characters, each richly drawn and achingly human: a Russian-born novelist; his Russian-born psychiatrist wife; their precocious child obsessed with K-pop; a struggling Indian American writer; a wildly successful Korean American app developer; a global dandy with three passports; a young flame-thrower of an essayist, originally from the Carolinas; and a movie star, The Actor, whose arrival upsets the equilibrium of this chosen family"--